Peran Guru Dalam Meningkatkan Budaya Literasi Terhadap Minat Baca Siswa di Sekolah Dasar - Karina Cahyani; Dinie Anggraeni Dewi; Rizky Saeful Hayat (International Forum of Researchers and Lecturers, 2024)
This research aims to explore the potential for strengthening literacy culture in elementary schools by focusing on the role of teachers as role models, facilitators and resource providers. The research method uses a qualitative approach with Systematic Literature Review (SLR) as an information gathering tool. The aim is to strengthen the implementation of literacy culture in schools through integration in the curriculum, increasing the role of parents, and a variety of books in the library. The benefits include increasing literacy understanding, student motivation to read, and the formation of a strong literacy culture in elementary schools. The results of this research note the positive impact of strengthening literacy culture, including increasing literacy understanding, student motivation to read, and the formation of a sustainable literacy culture in the elementary school environment. The teacher's role as a role model, facilitator and resource provider has a significant influence on the successful implementation of a literacy culture.